Caco-2 Cell Line Standardization with Pharmaceutical Requirements and In Vitro Model Suitability for Permeability Assays - Marta Kus; Izabela Ibragimow; Hanna Piotrowska-Kempisty (MDPI AG, 2023)
The Caco-2 cell line derived from human colon carcinoma is commonly used to assess the permeability of compounds in in vitro conditions. Due to the significant increase in permeability studies using the Caco-2 cell line in recent years, the need to standardize this biological model seems necessary. The pharmaceutical requirements define only the acceptance criteria for the validation of the Caco-2 cell line and do not specify the protocol for its implementation. Therefore, the aim of this study is to review the conditions for permeability studies across the Caco-2 monolayer reported in the available literature concerning validation guidelines. We summarized the main aspects affecting the validation process of the Caco-2 cell line, including the culture conditions, cytotoxicity, cell differentiation process, and monolayer transport conditions, and the main conclusions may be useful in developing individual methods for preparing the cell line for validation purposes and further permeability research.